Sulfonamide-Based Azaheterocyclic Schiff Base Derivatives as Potential Carbonic Anhydrase Inhibitors: Synthesis, Cytotoxicity, and Enzyme Inhibitory Kinetics. (21st February 2020) - Abas, Mujahid; Rafique, Hummera; Shamas, Shazia; Roshan, Sadia; Ashraf, Zaman; Iqbal, Zafar; Raza, Hussain; Hassan, Mubashir; Afzal, Khurram; Rizvanov, Albert A.; Asad, Muhammad Hassham Hassan Bin
Abstract : A series of sulfonamide-bearing azaheterocyclic Schiff base derivatives 3(a-j) were synthesized as carbonic anhydrase inhibitors. The substituted benzene sulfonyl chlorides 1(a-d) were reacted with N2 H4 to get aromatic sulfonyl hydrazides 2(a-d) . The intermediate hydrazides 2(a-d) were treated with substituted aldehydes to afford azaheterocyclic sulfonamide Schiff bases 3(a-j) . The spectral data of synthesized compounds confirmed the formation of the final products. The inhibitory effects of 3(a-j) on carbonic anhydrase activity were determined, and it was found that derivative 3c exhibited the most potent activity with IC50 0.84 ± 0.12   μ M among all other derivatives and is also more active than standard acetazolamide (IC50 0.91 ± 0.12 ). The enzyme inhibitory kinetics results determined by Lineweaver-Burk plots revealed that compound 3c inhibits the enzyme by noncompetitive mode of inhibition with K i value 8.6  μ M. The molecular docking investigations of the synthesized analogues 3(a-j) were evaluated which assured that synthesized compounds bind well inside the active binding site of the target enzyme. Cytotoxicity on human keratinocyte (HaCaT) and MCF-7 cell lines was performed, and it was found that most of the synthesized analogues were nontoxic on these cell lines and the toxic effects follow the dose-dependent manner. Based on our investigations, it was suggested that analogue 3c may serve as core structure to project carbonic anhydrase inhibitors with greater potency.